THU0184 Adherence profiles to methotrexate of patients with rheumatoid arthritis (RA) eligible for biologics: typologies from forget, a cross-sectional survey of 244 patients. (15th June 2017) - Beauvais, C; Hautin-Monteil, V; Ducrot, M-C; Flipo, R-M
Abstract : Background: Adherence to Methotrexate (MTX) is not optimal in RA patients [1]. Conflicting determinants of adherence have been identified in literature. Our hypothesis was that the discordant results were related to different typologies of patients. Objectives: Determine the Methotrexate adherence profiles of patients with RA eligible for biologics. Methods: The FORGET survey carried out in 2016 was aimed to assess the MTX adherence rate of RA patients, insufficient responders to MTX, biologic-naive, when an initiation of biologics was being considered. Non-adherence was defined as a compliance rate <80% according to the CQR19 (Compliance Questionnaire for Rheumatology) [2]. The factors tested were socio-demographic characteristics, DAS 28, RAID, CQR responses, beliefs, voluntary or involuntary dose skipping, social and medical support. Results: Of the 244 patients analyzed, the non-adherence rate was 34%. The rather weak correlation between adherence (CQR) and the disease impact (RAID) tended to confirm the hypothesis of different profiles. Four typologies of patients were determined. Groups G1 and G2 were non-adherent patients with high (G1) or lower (G2) impact. Groups G3 and G4 were patients with good adherence with high (G3) or lower impact (G4. Significant adherence factors were found for these 4 groups (p<0.01) (table). Conclusions: Four adherence profiles to Methotrexate have been identified. Among the non-adherent patients, 2 topologies are opposed: 1- patients in state of suffering, with low support from relatives, negative beliefs and significant professional impact. 2-patients with less disease impact, who perceived their treatment with constraints although well tolerated. Detection of patients' profiles may allow targeted strategies to improve or maintain adherence. References: DiBenedetti D Rheumatol Ther 2015. de Klerk E et al, J Rheumatol 1999. Acknowledgements: This study was funded by Chugai Pharma France. Disclosure of Interest: C. Beauvais: None declared, V. Hautin-Monteil Employee of: Roche France, M.-C. Ducrot: None declared, R.-M. Flipo: None declared